Registration of 'Bearpaw' Wheat. Issue 2 (25th January 2013) - Carlson, G. R.; Berg, J. E.; Stougaard, R. N.; Eckhoff, J. L.; Lamb, P. F.; Kephart, K. D.; Wichman, D. M.; Miller, J. H.; Riveland, N. R.; Nash, D. L.; Grey, W. E.; Jin, Y.; et al.
Abstract : 'Bearpaw' (Reg. No. CV‐1083, PI 665228) hard red winter (HRW) wheat ( Triticum aestivum L.) was developed and released by the Montana Agricultural Experiment Station in September 2011. Bearpaw is of unknown pedigree, derived from a composite of five crosses made to the same F1 male sterile parent in 1999: Dominant male sterile (DMS)/'Rampart'//'Pronghorn'/3/2*Rampart, DMS/Rampart//Pronghorn/3/Rampart/4/MTW9806, DMS/Rampart//Pronghorn/3/Rampart/4/'Nuplains', DMS/Rampart//Pronghorn/3/Rampart/4/MT9513, DMS/Rampart//Pronghorn/3/Rampart/4/MT98113. Bearpaw was developed using a modified bulk‐breeding method and selected as an F5:6 headrow. Bearpaw was tested under the experimental number MTS0721 from 2007 to 2011 in Montana. Quality has been evaluated in multilocation Montana trials since 2007. Bearpaw is a high‐yielding, solid‐stem, semidwarf (Rht‐B1b) HRW wheat cultivar with medium maturity, medium to high test weight and grain protein, and acceptable milling and baking quality. Bearpaw was released for its host‐plant resistance to wheat stem sawfly ( Cephus cinctus Nort.) conditioned by stem solidness, along with short stature and improved yield potential relative to existing solid‐stem cultivars adapted to Montana.